Ginkgo biloba in the Aging Process: A Narrative Review - Sandra Maria Barbalho; Rosa Direito; Lucas Fornari Laurindo; Ledyane Taynara Marton; Elen Landgraf Guiguer; Ricardo de Alvares Goulart; Ricardo José Tofano; Antonely C. A. Carvalho; Uri Adrian Prync Flato; Viviane Alessandra Capelluppi Tofano; Cláudia Rucco Penteado Detregiachi; Patrícia C. Santos Bueno; et al. (MDPI AG, 2022)
Neurodegenerative diseases, cardiovascular disease (CVD), hypertension, insulin resistance, cancer, and other degenerative processes commonly appear with aging. Ginkgo biloba (GB) is associated with several health benefits, including memory and cognitive improvement, in Alzheimer's disease (AD), Parkinson's disease (PD), and cancer. Its antiapoptotic, antioxidant, and anti-inflammatory actions have effects on cognition and other conditions associated with aging-related processes, such as insulin resistance, hypertension, and cardiovascular conditions. The aim of this study was to perform a narrative review of the effects of GB in some age-related conditions, such as neurodegenerative diseases, CVD, and cancer. PubMed, Cochrane, and Embase databases were searched, and the PRISMA guidelines were applied. Fourteen clinical trials were selected; the studies showed that GB can improve memory, cognition, memory scores, psychopathology, and the quality of life of patients. Moreover, it can improve cerebral blood flow supply, executive function, attention/concentration, non-verbal memory, and mood, and decrease stress, fasting serum glucose, glycated hemoglobin, insulin levels, body mass index, waist circumference, biomarkers of oxidative stress, the stability and progression of atherosclerotic plaques, and inflammation. Therefore, it is possible to conclude that the use of GB can provide benefits in the prevention and treatment of aging-related conditions.